Interferensi Bahasa Inggris pada Status Whatsapp Mahasiswa Semester 4 KIP STKIP Rokania SEMESTER 4 KIP STKIP ROKANIA - Uzlah Ilmi Irwan; Asih Ria Ningsih (Universitas Muhammadiyah Mataram, 2023)
The purpose of this study was to describe the interference of English word morphology on WhatsApp status of 4th semester students of KIP STKIP Rokania. To determine the interference in this article using a qualitative descriptive method and analyzed based on the content of the status. The theory used is Chaer's theory (1995) which states that the use of elements of other languages in using a language is considered a mistake because it deviates from the rules or rules of the language used. Bilingual or multilingual people often mix one language with another when uploading statuses on WhatsApp so that interference often arises. In this article, we will discuss several examples of morphological English interference in WhatsApp status with the aim of knowing the causes of language errors. The method used is descriptive qualitative method. The conclusion of this study is that interference often occurs due to lack of mastery of one language or intentional writing errors in order to follow the trend.